Example Data Supporting a Cross-Domain Transfer Learning Framework for Seismic Interpretation - Zhengfa Bi (22677614) (2025)
This repository contains the example seismic data used in our manuscript, serving as supplementary materials for demonstrating our cross-domain transfer learning framework for seismic interpretation. The following publicly available datasets are referenced in the manuscript: Netherlands F3 Block The Netherlands F3 block dataset is a widely used benchmark dataset in seismic interpretation studies. It can be downloaded from Zenodo: https://zenodo.org/records/1471548 (Referenced in: Alaudah et al., 2019; Silva et al., 2019) Teapot Dome Seismic Dataset The Teapot Dome 3D seismic dataset is provided by the Society of Exploration Geophysicists (SEG), as described in Chiaramonte et al. (2008). Access information is available through SEG’s data portal. Parihaka 3D Seismic Dataset The Parihaka 3D seismic dataset is publicly available and can be downloaded from the SEG Wiki: https://wiki.seg.org/wiki/Parihaka-3D If you use the datasets linked above, please cite their original authors and data sources accordingly.